Controlling and preventing the actions of the foreign agents. A relevant order for the county structures of the Securitate UM 0110 from 2nd of December 1989 - ȚÂRĂU, Virgiliu (Studia Universitatis Babeș-Bolyai Historia, 2020)
Thirty years after the fall of communism the debates about the soviet role in the East European Revolutions of 1989 are not ended. In this short article we discuss a relevant document in relation with this topic. It was an order issued by the Chief of the UM 0110 at the beginning of December 1989 in relation with the dangers related to the presence of tourists form East and West in Romania. In essence, in the same day when supposedly Bush and Gorbachev discussed in Malta the fate of Romania, the UM 0110 enter in an alarm situation. According to the directive, in order to control and prevent, but also for neutralize and thwart any hostile actions of the possible dangers, the UM 0110 need to intensify the surveillance of different categories of subjects which were in the attention (foreign tourists, other foreign travelers or representatives that were in Romania from other communist countries). What this document tells us is the fact that the Romanian Securitate was aware that such dangers need to be addressed urgently and that beyond routine urgent actions need to be prepared. These perils become pressing in terms of control, prevention and neutralization of the eventual actions of those tourists. Rezumat: La treizeci de ani de la căderea regimurilor comuniste, dezbaterile despre rolul jucat de sovietici în Revoluţiile din 1989 din Estul Europei încă nu s-au încheiat. În scurtul nostru articol vom discuta un document relevant în relaţie cu acest subiect. Este vorba de un ordin emis de şeful Unităţii Militare 0110 la începutul lunii decembrie 1989 cu privire la prezenţa unor pericole legate de prezenţa în România a unor turişti din Est şi Vest. De fapt în ziua în care, speculativ se afirmă că, la Malta, George Bush şi Mihail Gorbaciov discutau despre soarta României, Securitate prin unitatea ei specială dedicată urmăririi şi supravegherii cetăţenilor din statele comuniste a intrat în stare de alertă. În acord cu directivele date în ordin, pentru a controla şi preveni, dar şi pentru a neutraliza şi a face imposibile orice acţiuni ostile, UM 0110 trebuia să intensifice toate acţiunile de supraveghere şi control asupra categoriilor de persoane care intrau în atenţia sa (turişti sau reprezentanţi ai altor state comuniste aflaţi pe teritoriul României. Ceea ce documentul ne indică este faptul că Securitatea nu doar că a fost preparată să gestioneze acest tip de pericol, dar au fost elaborate şi ordine precise, dincolo de supravegherea obişnuită, pentru a preveni, neutraliza şi controla acţiunile venite din partea acestor turişti. Cuvinte-cheie: România, Decembrie 1989, turişti străini, supravegherea Securităţii, UM 0110.